2006
DOI: 10.1207/s15327027hc1901_4
|View full text |Cite
|
Sign up to set email alerts
|

Female Adolescent Communication About Sexually Transmitted Diseases

Abstract: Health researchers acknowledge a limited understanding of the social context of adolescents regarding their communication and decision making about sexually transmitted diseases (STDs). Using in-depth interviews, this study examines 18-year-old women regarding their self-concepts about STD communication, including their perceived and actual knowledge levels. Fifteen first-year college students from a Western university showed strong self-concepts and high perceived knowledge relative to sexual decision making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Similarly, much research exists on actual versus perceived knowledge about STDs [2]. Within the extant communication literature, little research exists regarding individuals communicating reasons for (not) disclosing a positive STD status and the reception of such a disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, much research exists on actual versus perceived knowledge about STDs [2]. Within the extant communication literature, little research exists regarding individuals communicating reasons for (not) disclosing a positive STD status and the reception of such a disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Although youth in the larger population rely on media for information about the prognosis, treatment, prevention, and meaning of health issues (Clark, 2004), they demonstrate preferences for talking with peers (Rouner & Lindsey 2006). They might use professional sources after speaking with peers, possibly checking for validation in media.…”
Section: Keyterms American Indians Health Communication Native Amermentioning
confidence: 99%
“…Further, channel complementarity has been demonstrated to be important among media channels and between interpersonal and media channels, as well as related to the severity of a health domain (Robinson, 2008). Given the importance of peers by American youth in sexual health information seeking (Rouner & Lindsey 2006), along with the abundance of information available online, this study assumed Native American youth are actively motivated to seek sexual health information. This study sought to better understand which content and channels are most salient and relevant to them.…”
Section: Keyterms American Indians Health Communication Native Amermentioning
confidence: 99%
See 1 more Smart Citation
“…Under these circumstances, people may unknowingly infect others. Not all sexually active students are aware of their HIV status; Rouner and Lindsey (2006) found that young people report feeling confident in their knowledge of HIV and STDs, but few demonstrated this knowledge in relation to the symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%